Rapid quantitative detection system for measles virus-neutralizing antibodies using HiBiT-tagged virus-like particles - Okura, Takashi; Miyakawa, Kei; Tahara, Maino; Someya, Kenji; Seki, Fumio; Nishi, Mayuko; Otsuki, Noriyuki; Ryo, Akihide (Microbiology and immunology, 2024)
Immunological testing to detect neutralizing antibodies (NAbs) is important in measles (MV) infection control. Currently, the plaque reduction neutralization test is the only credible method for measuring actual virus NAbs; however, its feasibility is hampered by drawbacks, such as long turnaround times, low throughput, and the need for laboratory biosafety equipment. To solve these problems, we developed a simple and rapid MV-NAb detection system using lentivirus-based virus-like particles incorporated with the NanoLuc fragment peptide HiBiT comprising the MV fusion protein and hemagglutinin on their exterior surface. Overall, this simple, safe, and rapid method could be used to detect MV NAbs.